The role of intestinal microbiota in energetic metabolism: new perspectives in combating obesity - Perpétuo, Juliana Pereira; Wilasco, Maria Inês de Albuquerque; Schneider, Ana Cláudia Reis (Clinical and Biomedical Research, 2015)
The knowledge that the composition of intestinal microbiota is different in lean and obese humans indicates that the microbiota plays an important role in the pathophysiology of obesity. Studies show that diet composition promotes the modification of intestinal bacterial species, favoring the increase of energy extraction from the diet, insulin resistance and obesity. Unbalanced diets, with overload fat and low fiber content, lead to increased Firmicutes and Proteobacteria phyla favoring dysbiosis, endotoxemia and inflammation. The use of probiotics, prebiotics and symbiotics, in order to modulate the composition of intestinal microbiome, may be a promising therapy for the reduction of the metabolic complications of obesity; however, further studies should be conducted to establish which probiotic species are suitable to help in the treatment of obesity.